(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes modern approaches aimed at improving the effectiveness of the work of educating students of higher educational institutions in the spirit of national values and loyalty to the motherland. The information provided is the most relevant issue of today when further development of the system of improving the education of students in higher educational institutions in the spirit of national values and loyalty to the motherland, as well as the education of their students in the spirit of national values and loyalty to the motherland.